Pengaruh Kepemimpinan, Budaya Kerja dan Motivasi Kerja Terhadap Loyalitas Kerja Karyawan : Studi Kasus Pada PT. Mata Air Persada - Delpiero, Francisco Enrico; Anwar, Syaiful (CNPLUS Publisher, 2024)
This research aims to determine the influence of Leadership (X1), Work Culture (X2) and Work Motivation (X3) on Employee Work Loyalty of PT. Mata Air Persada. The research method used is a quantitative method and the data collection technique uses a questionnaire with a Likert scale. The sample population in this study was 30 employees of PT. Mata Air Persada. In this study, non-probability sampling was used, namely a saturated sample. So the withdrawal sample is taken by the census. Data Analysis Techniques using Multiple Linear Regression. Research shows that (1) Leadership influences Employee Work Loyalty, (2) Work Culture influences Employee Work Loyalty, (3) Work Motivation influences Employee Work Loyalty. The results in this research show that work culture has a dominant influence on employee work loyalty